2007
DOI: 10.1002/jcp.20988
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐2 promotes differentiation of osteoblasts and chondroblasts in Runx2‐deficient cell lines

Abstract: To investigate the molecular mechanism underlying the differentiation of osteoblasts and chondroblasts, we established a clonal cell lines, RD-C6, from Runx2-deficient mouse embryos. RD-C6 cells expressed almost undetectable levels of phenotypes related to osteoblast and chondroblast differentiation at basal culture condition, whereas treatment with recombinant human bone morphogenetic protein-2 (rhBMP-2) or transduction of BMP-2 by adenovirus effectively induced this cell line to express mRNA related to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 35 publications
7
75
0
Order By: Relevance
“…Other factors, including Sox9, may play a role in Runx2-independent chondrocyte differentiation, although additional work is necessary to clearly identify these factors. 40 Thus, our data support the hypothesis that SMC-specific removal of Runx2 prevents both endochondral and intramembranous ossification in atherosclerotic lesions. In contrast to our studies, Sun et al 21 reported a role for SMC autonomous Runx2 in macrophage accumulation and atheromatous lesion formation using a very different Runx2 targeting construct.…”
Section: Discussionsupporting
confidence: 87%
“…Other factors, including Sox9, may play a role in Runx2-independent chondrocyte differentiation, although additional work is necessary to clearly identify these factors. 40 Thus, our data support the hypothesis that SMC-specific removal of Runx2 prevents both endochondral and intramembranous ossification in atherosclerotic lesions. In contrast to our studies, Sun et al 21 reported a role for SMC autonomous Runx2 in macrophage accumulation and atheromatous lesion formation using a very different Runx2 targeting construct.…”
Section: Discussionsupporting
confidence: 87%
“…The cells showed ALP activity. Runx2-deficient mesenchymal cells were isolated from the calvariae of Runx2-deficient embryos as described previously (17). In brief, the anterior region of calvariae from an embryo at embryonic day 18.5 was minced and cultured for 10 -14 days in three-dimensional collagen gel (Cellmatrix, Nitta Gelatin Co.) with ␣-modified minimum Eagle's medium containing 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the anterior region of calvariae from an embryo at embryonic day 18.5 was minced and cultured for 10 -14 days in three-dimensional collagen gel (Cellmatrix, Nitta Gelatin Co.) with ␣-modified minimum Eagle's medium containing 10% fetal bovine serum. The cells outgrowing from the explants were retrieved by incubation for 30 min with 0.2% collagenase in phosphate-buffered saline (PBS) at 37°C and then cultured with ␣-modified minimum Eagle's medium containing 10% fetal bovine serum (17).…”
Section: Methodsmentioning
confidence: 99%
“…A modified micromass culture technique was carried out, as previously described (21)(22)(23). Transfections were carried out using Lipofectamine 2000 (Invitrogen) in 6-well plates as per the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%